Perspectives on cross-cultural, ethnographic, brand image, storytelling, unconscious needs, and hospitality guest research - Woodside, Arch; Megehee, Carol M.; Ogle, Alfred (Emerald, 2009)
Volume 3 examines how research tools affect theory advances in culture and tourism research. Using visual narrative art to explicate unconscious thinking that shapes trip plans and visits, building tree diagrams of streams of antecedent conditions associating with extreme behavior (e.g., road rage, chronic casino gambling), and research methods that go beyond quantitative/qualitative taxonomies are examples of the unique themes covered in this volume. The papers focus on how to gain meaning from data to thus look at how streams of antecedent conditions result in tourism behavior.
Includes index.
Keywords: Tourism.; Hospitality industry.; elektronické knihy; electronic books